Mapping breastfeeding and COVID-19 related content and engagement on Facebook: Results from an online social listening study - White, Becky; Burns, Sharyn; Carson, Jennie; Scott, Jane (2023)
ISSUE ADDRESSED: The COVID-19 pandemic has seen evidence and advice evolve quickly. Since the start of the pandemic there has been confusion and concern about breastfeeding and COVID-19, and advice for this group has at times been contradictory. The volume of information on social media has exacerbated this. This study aimed to understand breastfeeding-related COVID-19 information sharing on social media during the global and Australian vaccine roll-out. METHODS: The CrowdTangle platform was used to source data from December 2020 to December 2021. Posts were categorised to intent and source and mapped to a timeline of pandemic-related events and announcements. Descriptive analysis was used to understand data distribution patterns and qualitative analysis for post intent. RESULTS: A total of 945 posts were included. Post interactions ranged from 0-6,500. Vaccine-related posts were the highest in number and increased over time. Non-Profit Organisations shared the highest number of posts (n=241), but interactions were highest with personal and government accounts. Peaks in posts and interactions mapped to key pandemic-related announcements and events. CONCLUSION: These results describe the breastfeeding and COVID-19 related content shared on Facebook over 13 months, and the associated interactions. Breastfeeding is an important public health issue and breastfeeding women have experienced conflicting and confusing breastfeeding-related information during the COVID-19 pandemic. Better understanding of social media usage, and the monitoring of changes in usage, as an emergency unfolds, can help target communications. This paper adds to the evidence in understanding user reactions to COVID-19 related breastfeeding information on social media. SO WHAT?: Social listening is an important part of health communication and infodemic management. Understanding how users react to and engage with COVID-19 related breastfeeding information on social media can help to understand how the general public perceives and responds to health advice and other information being shared.